A Communication Protocol Design aimed at a Multi-Agent System Framework for Miniaturized Satellite Systems - Samantha Iteriano-Valverde; David Scazzoli; Carmen Chan-Zheng; Johan Carvajal-Godinez; Mauricio Magarini (Tecnología en Marcha)
In recent years space-science and exploration have become more accessible due to the popularization of the concept of CubeSats. CubeSats are being used as a result of their convenient size and weight requirements, allowing for target missions to be designed, developed, and launched with a significant reduction of costs compared to traditional space missions.  Furthermore, the development of target missions has become more intricate, forcing a shift in the traditional notion of using a centralized control architecture to a distributed architecture.  A distributed architecture tackles the problem of a possible functionality loss over the control unit. This paper describes the extension of capabilities of the Multi-Agent Systems Framework for Embedded Systems (MAES). This extension provides MAES framework with the ability to perform inter-platform communication, so now the control unit architecture can be broadened allowing agents from different platforms to interact and perform cooperatively different routines designed by the developer, so it is not limited to the capabilities of just one platform. Moreover, this paper shows the results of the experimental setup showing the precision of inter-platform message exchange and the relationship between the delay of the exchange of inter-platform messages and the number of agents that are simultaneously running on each platform.